Report of the International Conference in Sport Science "ICSS 2019" of the Sports University of Tirana - Juel Jarani (University of Montenegro, Faculty for Sport and Physical Education, Montenegrin Sports Academy, 2020)
The article is providing highlights of the Report of the International Conference in Sport Science "ICSS 2019", hosted by the Sports University of Tirana. The event was held on December 6-7, 2019 in Tirana, Albania. The Conference provided space for presentation research papers and related discussion, as well as for poster sessions. The Conference was officially opened in the large conference hall of the Sports University of Tirana by prof. Agron Cuka, PhD, Rector of the Sports University of Tirana and chairman of the Conference scientific committee. This prestigious event gathered 264 authors and 84 participants, coming from 7 countries.